Effect of in-situ stress contrast on fracture containment during single- and multi-stage hydraulic fracturing. (January 2019) - Wasantha, P.L.P.; Konietzky, H.; Xu, C.
Highlights: Stress shadowing leads to an asymmetric fracture propagation during multi-stage fracturing. In-situ stress contrast can constrain the fracture propagation to some extent. Fluid injection time needs to be optimized to contain the fractures within pay zone. Abstract: Hydraulic fracture containment behaviour under varying in-situ stress conditions was studied for single- and multi-stage hydraulic fracturing using a fully coupled hydro-mechanical model. Single-stage fracturing under varying and non-varying minor principal stress conditions showed good agreement with the corresponding analytical predictions. Multi-stage fracturing under non-varying stress conditions displayed a strong stress shadow-induced asymmetry of fracture propagation about the injection well. As the fluid pressure dissipation after fracturing in the numerical simulations is assumed to be negligible before the subsequent fracturing stage, it was observed that the fractures can extend even after the actual injection time as a result of the stress shadow generated during subsequent fracturing stages. The stress contrast between adjoining layers and the pay zone was found to be somewhat effective in containing fractures within the pay zone, although the asymmetry of fracture profiles was still apparent. It was also observed that the stress shadow effect is sufficiently significant in some cases that the fractures have the preference to penetrate into higher stress adjoining layers than propagating within the initially lower-stress pay zone, which is generally unfavourable. Fluid injection time was found to have a major influence on overall fracture propagation during multi-stage fracturing and the fractures were observed to be fully and only within the pay zone, delineating the effective containment, for simulations with optimized injection times. In addition, our simulations show that, based on the fact that fractures can be further driven by the stress shadows of subsequent fracturing stages, strategically-selected injection times for each fracturing stage can produce fractures that fully and only occupy the pay zone, which can save a considerable amount of injection fluid. This has direct positive implications for project economics and will help minimize potential issues associated with deep fluid injection, such as groundwater contamination and induced seismicity.